Heavy Users, Mobile Gamers, and Social Networkers: Patterns of Objective Smartphone Use in Parents of Infants and Associations With Parent Depression, Sleep, Parenting, and Problematic Phone Use - Brandon T. McDaniel; Jenny Radesky; Jessica Pater; Adam M. Galovan; Annalise Harrison; Victor Cornet; Lauren Reining; Alexandria Schaller; Michelle Drouin (Human Behavior and Emerging Technologies)
Smartphone use during parenting is common, which may lead to distraction (also known as technoference). However, it is likely that some phone activities are less disruptive to parents and children. In this study, we explored smartphone use (via passive sensing across 8 days) within 264 parents of infants, measuring parents’ application use on their phone (e.g., messaging, social media, mobile gaming, video chat) and phone use across contexts (e.g., during feeding and at bedtime). We utilized latent profile analysis to identify profiles of users, revealing five user types: Moderate User Social Networkers (37%), followed by Moderate User Gamers (20%), Moderate User Video Chatters (17%), Low Users (15%), and Heavy Users (11%). Parents varied in their use, from Low Users, who used their phone approximately 2.4 h each day, spent only 13% of their child time on their phone, and used their phone for about 18 min at bedtime, to Heavy Users, who spent approximately 8 h a day, about 50% of their child time on their phone, and about 1 h at bedtime. Heavy Users showed higher depressive symptoms and poorer sleep (although not poorer sleep than Moderate User Gamers). Surprisingly, we found no differences between groups in perceptions of parenting stress, responsiveness to their infant, or problematic phone use and distraction. We also explored demographic differences across groups. We call for future work to examine parent phone use more comprehensively and holistically and to view specific phone use activities as simultaneously interconnected with other types of use activities.